Pengaruh Implementasi Sistem Informasi Manajemen Daerah (SIMDA) Keuangan Terhadap Kualitas Laporan Keuangan (Studi pada Lingkungan Dinas Kesehatan Kabupaten Padang Pariaman) - Febryandhie Ananda; Mustika Permata Sari (JURNAL PUNDI, 2020)
The purpose of this study was to examine the effect of SIMDA on the Quality of Financial Statements at the Health Service Unit UPT. This research is based on the results of testing of 110 respondents at the Health Service UPT. This study uses research respondents who are directly distributed and uses multiple linear regression techniques to test research data with the help of SPSS 25. This study uses SIMDA one dependent variable, namely: Quality of Financial Statements. The results showed that partially, SIMDA had a significant influence on the quality of financial statements Keywords: SIMDA, Quality of Financial Statements